Efficient size control of copper nanoparticles generated in irradiated aqueous solutions of star-shaped polyelectrolyte containers. Issue 17 (7th May 2015) - Zezin, Alexey A.; Feldman, Vladimir I.; Abramchuk, Sergei S.; Danelyan, Gurgen V.; Dyo, Victor V.; Plamper, Felix A.; Müller, Axel H. E.; Pergushov, Dmitry V.
<x xml:space="preserve">Abstract</x> Star-shaped poly(acrylic acid) macromolecules act as nanoreactors for the preparation of narrow-dispersed copper nanoparticles by radiation-induced reduction of copper(ii) ions.